Modification method of nano silicon dioxide and modified asphalt

By agglomerating polyethylene glycol on the surface of nano silica and carrying out cycloalkane grafting reaction, the problem of density difference between nano silica and asphalt is solved, and the storage stability and anti-aging of modified asphalt are improved performance.

CN119490694APending Publication Date: 2025-02-21CHINA PETROLEUM & CHEMICAL CORP +1

Patent Information

Application Number
CN202311018996.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-08-14
Publication Date
2025-02-21

AI Technical Summary

Technical Problem

The density difference between nanosilicon dioxide and asphalt causes nanoparticles to settle, reducing the storage stability and anti-aging properties of modified asphalt.

Method used

The nanosilica is coated with aqueous polyethylene glycol solution and grafted in a cycloalkane solution to enhance the mutual solubility and compatibility of the nanosilica and asphalt.

Benefits of technology

The mutual solubility and compatibility between nanosilicon dioxide and asphalt are improved, the nanoparticles are prevented from sedimentation, and the storage stability and anti-aging properties of modified asphalt are enhanced.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention discloses a modification method of nano silicon dioxide and modified asphalt, and belongs to the technical field of asphalt modifiers or silicon compounds. Nano-particles are easy to settle in the modified asphalt due to different densities when the nano-materials are used for modifying the asphalt, so that the storage stability of the modified asphalt is poor, and after the nano-particles settle, the nano-particles are mutually gathered, so that the viscosity of the nano-modified asphalt is greatly increased, and the asphalt is fractured. The preparation method comprises the following steps: 1) stirring and mixing nano silicon dioxide and a thickening agent dispersion liquid, separating, washing and drying to obtain nano silicon dioxide coated with a thickening agent; wherein the thickening agent is a polyethylene glycol aqueous solution; and 2) adding the nano-silica coated with the thickening agent into the naphthenate solution, and carrying out constant temperature reaction, separation, washing and drying to obtain the modified nano-silica, the solvent in the naphthenate solution being a benzene solvent, so that the intersolubility of the nano-silica and asphalt is improved, network winding is formed, and the settling resistance of nano-silica particles is increased.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention discloses a modification method of nano silicon dioxide and modified asphalt, belonging to the technical field of asphalt modifiers or silicon compounds. Background Art

[0002] Since nanomaterials have a high specific surface area, when they are added to modified asphalt, the mechanical, thermal and other properties of modified asphalt can be greatly improved. However, the density of nanomaterials is greater than that of asphalt. When they are added to modified asphalt, the different densities of the two cause the nanoparticles to settle in the modified asphalt, resulting in poor storage stability of the modified asphalt. After settling, the nanoparticles aggregate with each other, which will cause the viscosity of the nano-modified asphalt to increase significantly. In addition, the nanomaterials that settle at the bottom will cause the modified asphalt to break easily here, affecting the low-temperature performance of the modified asphalt. At the same time, the nanoparticles that settle at the bottom are isolated from contact with oxygen in the air at high temperatures, and cannot play the role of the nanomaterials in improving the anti-oxidation ability of asphalt, so that the anti-aging property of the modified asphalt cannot be improved.

[0003] At present, the modification of nanomaterials mainly includes surface modification and polymer coating, but the modifiers used for surface modification are all low molecular weight, short molecular chain substances, such as silane coupling agents, oleic acid, stearic acid and other substances, and have poor solubility with the matrix asphalt, and cannot solve the problem of density difference between nanomaterials and asphalt; and in the polymer coating technology, during the high-temperature preparation of modified asphalt, the polymer will dissolve, resulting in the failure of the coating effect, and when the polymer is coated, the nanomaterial cannot directly contact with the asphalt, and the modification effect of the nanomaterial cannot be exerted.

[0004] Patent CN103013182A discloses a method for surface modification of nano-silica, which uses KH-550 to ultrasonically modify the surface of silica nanoparticles, thereby improving the dispersibility and anti-aging properties of the silica nanoparticles. However, this method has limited surface modification capabilities for nano-silica in actual applications and has limited effects on improving dispersibility.

[0005] Patent CN108274844B discloses the use of SBS modifiers and polyamide wax to improve the dispersibility of nano-silica and nano-zeolite in asphalt, but the nano-silica itself does not actually change its surface, and the slow separation of asphalt as inorganic and organic components during long-term use is still not effectively improved. Summary of the invention

[0006] The technical problem to be solved by the present invention is to overcome the deficiencies of the prior art and provide a method for modifying nano-silicon dioxide and modified asphalt that solves the problems of mutual solubility and stability between nano-silicon dioxide and asphalt.

[0007] The technical solution adopted by the present invention to solve the technical problem is: a method for modifying nano silicon dioxide, characterized in that it comprises the following steps: 1) The nano-silica and the thickener dispersion are stirred and mixed for 30-60 minutes, and then separated, washed and dried to obtain the nano-silica coated with the thickener; wherein the thickener is a polyethylene glycol aqueous solution with a weight concentration of 1-3%; 2) Adding nano-silica coated with a thickener to a cyclopentane acid solution with a weight concentration of 15-25%, reacting at a constant temperature of 60-80° C. for 180-240 minutes, separating, washing and drying to obtain modified nano-silica; wherein the solvent in the cyclopentane acid solution is a benzene solvent.

[0008] Nano-silica is dispersed by using polyethylene glycol aqueous solution, so that the thickener is evenly coated on the surface of the nano-silica particles to prevent the nano-silica particles from self-aggregating. In step 2), polyethylene glycol is miscible with cyclopentane acid esters and benzene solvents. The silica particles coated with the thickener are added to the reaction system. The thickener coated on the surface of the nano-silica particles will quickly dissolve in the reaction system, releasing the nano-silica particles, which is beneficial to the grafting reaction and also improves the grafting rate. Cycloalkane esters are generated by the esterification reaction of cycloalkane acid and alcohol, and have a longer main chain and more and longer side chains. At the same time, cycloalkane acid is derived from petroleum components and has good miscibility with petroleum asphalt. When it is grafted to the surface of nano-silica particles through the above-mentioned modification method, the miscibility of the nano-silica particles and the matrix asphalt is increased, and the long organic chains on the surface of the nano-silica particles can be entangled with heavy components such as asphaltenes and colloids in the matrix asphalt to form a network entanglement, which increases the sedimentation resistance of the nano-silica particles, limits the downward movement of the nano-silica particles, and can prevent the nano-silica particles from settling in the asphalt due to their own high density, thereby improving the storage stability of the nano-modified asphalt.

[0009] Preferably, the polyethylene glycol in step 1) is one or both of PEG-4000 and PEG-6000. The preferred polyethylene glycol has high water solubility, high molecular weight, good thickening effect, and easy to control viscosity.

[0010] Preferably, the polyethylene glycol aqueous solution in step 1) is prepared by mixing deionized water and thickener, and then mixing at 50-70°C and stirring at 300-500 rpm for 20-40 minutes. Under the preferred method, the thickener can form a relatively uniform colloidal liquid, and the thickener is more uniform, which is suitable for dispersing nano-silicon dioxide and avoiding self-aggregation of nano-silicon dioxide in the system.

[0011] Preferably, the stirring and mixing speed in step 1) is 4000-6000 rpm. Preferably, the benzene solvent in step 2) is xylene. Xylene and polyethylene glycol have good solubility and can quickly dissolve the solubilizing agent on the surface of nano-silicon dioxide.

[0012] A modified asphalt, characterized in that the raw materials include, by weight, 85-92 parts of base asphalt, 4-8 parts of modifier, 1-4 parts of solubilizer, 0.2-0.3 parts of stabilizer and 1.7-4.8 parts of the modified nano silicon dioxide mentioned above.

[0013] Preferably, the solubilizing agent is naphthenic oil, and its kinematic viscosity at 40°C is less than 50 mm 2 / s.

[0014] Preferably, the modifier is SBS polymer.

[0015] More preferably, the melt flow rate is 0.1 to 5 g·10 min -1 .

[0016] The base asphalt has a softening point of ≥46°C and a needle penetration of 60 to 70. The stabilizer is a mixture of sulfur powder and carbon powder in a weight ratio of 1:1.

[0017] Preferably, the preparation method comprises the following steps: 1) Mix the base asphalt and the solubilizer at 170-180°C and a stirring speed of 800-1000 rpm for 30-50 min, add nano-silicon dioxide, and react at 170-180°C and a stirring speed of 3000-4000 rpm for 20-40 min; 2) Add the modifier, react at 170-180°C and stirring speed of 3000-4000 rpm for 60-80 minutes, and then place in an oven at 140-150°C for constant temperature development for 60-100 minutes to obtain modified asphalt.

[0018] Premixing the base asphalt with the solubilizer can reduce the viscosity of the base asphalt, accelerate the rapid contact between the modified nano-silicon dioxide particles and the asphalt, and further improve the compatibility of the nano-silicon dioxide and the base asphalt.

[0019] Preferably, the base asphalt described in step 1) is kept at a constant temperature of 130-140° C. for 40-50 minutes before mixing.

[0020] Compared with the prior art, the present invention has the following beneficial effects: the surface of nano-silica is modified by a specific thickener and a grafting component, and cyclopentane acid esters are utilized to have a longer main chain and more and longer side chains. At the same time, cyclopentane acid is derived from petroleum components and has good miscibility with petroleum asphalt, which greatly improves the miscibility of nano-silica and asphalt. In addition, the organic long chains on the surface of nano-silica particles can be entangled with heavy components such as asphaltene and colloid in the matrix asphalt to form a network entanglement, which increases the sedimentation resistance of the nano-silica particles, limits the downward movement of the nano-silica particles, and can prevent the nano-silica particles from settling in the asphalt due to their own high density, thereby improving the storage stability of the nano-modified asphalt. DETAILED DESCRIPTION

[0021] The present invention will be further described below in conjunction with the embodiments, and Embodiment 2 is the best embodiment of the present invention.

[0022] In the following examples and comparative examples, the base asphalt softening point is ≥46°C, the needle penetration is 60-70, and the needle penetration is measured according to the method of GB / T4509-2010. The modifier is SBS polymer produced by Sinopec Baling Branch: S / B (weight ratio) is 30 / 70, and the melt flow rate is 0.1-5 g·10 min -1 The solubilizer is cyclohexane oil, with a flash point greater than 230°C and a kinematic viscosity of less than 50 mm at 40°C. 2 / s. The stabilizer is a mixture of sulfur powder and carbon powder in a weight ratio of 1:1.

[0023] Example 1 A method for modifying nano silicon dioxide comprises the following steps: 1) Polyethylene glycol PEG-4000 and deionized water were mixed in a weight ratio of 1:99, mixed at 60°C and a stirring speed of 400 rpm for 30 minutes, then the speed was increased to 5000 rpm, and nano-silica powder was slowly added, and stirring was continued for 50 minutes. The product was centrifuged, rinsed with deionized water, and placed in an oven at 80°C for constant temperature drying for 70 minutes to obtain nano-silica coated with a thickener.

[0024] 2) Cyclopentane acid ester and xylene were mixed in a weight ratio of 0.2:1, and then the nano-silica coated with thickener was added at a speed of 700 rpm, the temperature was raised to 70°C, the reaction was carried out at a constant temperature for 200 minutes, and the modified nano-silica was obtained by centrifugation, washing and drying.

[0025] A modified asphalt, the raw materials of which include 92 kg of base asphalt, 4 kg of modifier, 2 kg of solubilizer, 0.3 kg of stabilizer and 1.7 kg of modified nano silicon dioxide.

[0026] The preparation method of modified asphalt is: 1) Place the base asphalt in an oven at a constant temperature of 135°C for 50 minutes; add a solubilizer and mix at 175°C and a stirring speed of 900 rpm for 40 minutes; then add modified nano-silica by weight and react at 175°C and a stirring speed of 3500 rpm for 30 minutes.

[0027] 2) Add the modifier and continue stirring the reaction at 175°C and 3500 rpm for 70 minutes; finally, add the stabilizer and continue the reaction for 35 minutes, then place in an oven at 145°C and develop at a constant temperature for 80 minutes to obtain the modified asphalt.

[0028] Example 2 A method for modifying nano silicon dioxide adopts the same modification method as that in Example 1.

[0029] A modified asphalt, based on Example 1, the raw materials are set as 85 kg of base asphalt, 8 kg of modifier, 3 kg of solubilizer, 0.3 kg of stabilizer, and 3.7 kg of modified nano-silicon dioxide. Other conditions are the same as in Example 1.

[0030] Example 3 A method for modifying nano silicon dioxide adopts the same modification method as that in Example 1.

[0031] A modified asphalt, based on Example 1, the raw materials are set as 88 kg of base asphalt, 6 kg of modifier, 1 kg of solubilizer, 0.2 kg of stabilizer, and 4.8 kg of modified nano-silicon dioxide. Other conditions are the same as in Example 1.

[0032] Example 4 A method for modifying nano silicon dioxide adopts the same modification method as that in Example 1.

[0033] A modified asphalt, based on Example 1, the raw materials are set as 85 kg of base asphalt, 5 kg of modifier, 3 kg of solubilizer, 0.3 kg of stabilizer, and 2.7 kg of modified nano-silicon dioxide. Other conditions are the same as in Example 1.

[0034] Example 5 A method for modifying nano silicon dioxide adopts the same modification method as that in Example 1.

[0035] A modified asphalt, based on Example 1, the raw materials are set as 90 kg of base asphalt, 6.5 kg of modifier, 1 kg of solubilizer, 0.2 kg of stabilizer, and 2.3 kg of modified nano-silicon dioxide. Other conditions are the same as in Example 1.

[0036] Example 6 A method for modifying nano silicon dioxide adopts the same modification method as that in Example 1.

[0037] A modified asphalt, based on Example 1, the raw materials are set as 87 kg of base asphalt, 7 kg of modifier, 4 kg of solubilizer, 0.2 kg of stabilizer, and 1.8 kg of modified nano-silicon dioxide. Other conditions are the same as in Example 1.

[0038] Example 7 A method for modifying nano-silicon dioxide, based on Example 1, step 1) polyethylene glycol is replaced with PEG-6000. The weight ratio of polyethylene glycol to deionized water is set to 3:97. Step 2) the weight ratio of cyclohexane acid ester to xylene is set to 0.3:1. Other conditions and the preparation method of modified asphalt are the same as those in Example 1.

[0039] Comparative Example 1 A modified asphalt, based on Example 1, the modified nano-silicon dioxide is replaced by unmodified nano-silicon dioxide particles, and other conditions are the same as those of Example 1.

[0040] Comparative Example 2 A method for modifying nano silicon dioxide is provided. Based on Example 1, step 2) is not provided, and only step 1) is used to treat the nano silicon dioxide. Other conditions and the method for preparing the modified asphalt are the same as those in Example 1.

[0041] Comparative Example 3 A method for modifying nano silicon dioxide is provided. Based on Example 1, step 1) is not provided, and step 2) is directly performed on the nano silicon dioxide. Other conditions and the method for preparing modified asphalt are the same as those in Example 1.

[0042] Comparative Example 4 Anhydrous ethanol and deionized water were mixed in a weight ratio of 3:1, and silane coupling agent was slowly added. The mixture was mixed and reacted for 40 minutes at 50°C and a stirring speed of 400r / min to obtain a silane coupling agent hydrolysis solution, and the temperature was raised to 75°C, and the nano-SiO2 dispersion was slowly added. The reaction was continued for 200 minutes. The product was centrifuged, rinsed with ethanol, and placed in an 80°C oven for constant temperature drying for 60 to 80 minutes to obtain silane coupling agent modified nano-SiO2.

[0043] Comparative Example 5 A modification method of nano silicon dioxide comprises the following steps: Stearic acid and xylene were mixed at a mass ratio of 0.2:1, and then nano-SiO2 was uniformly dispersed therein under stirring conditions, and the mixture was reacted at a constant temperature of 70°C for 200 minutes. The mixture was centrifuged, washed, and dried to obtain modified nano-SiO2.

[0044] Comparative Example 6 A modified asphalt, based on Example 1, the preparation method is set as follows: under the conditions of 175°C and a stirring speed of 900 rpm, a solubilizer is added to the base asphalt, the rotation speed is set to 3500 rpm, and then modified nano-silicon dioxide, a modifier and a stabilizer are added in sequence, and the mixture is grown at a constant temperature of 145°C and a stirring speed of 3500 r / min for 80 minutes. The base asphalt, the solubilizer and the modified nano-silicon dioxide are not pre-mixed. Other conditions are the same as in Example 1.

[0045] Comparative Example 7 A modified asphalt, based on Example 1, without adding nano silicon dioxide, and other conditions are the same as Example 1.

[0046] Performance Testing The modified asphalt obtained in the above examples and comparative examples was subjected to performance tests. The performance test results are shown in Table 1 below.

[0047] Among them, the softening point is measured according to GB / T 4507-2010, the rotational viscosity at 135°C is measured according to T0625-2011, the aging is measured according to SH / T 0736-2003, and the asphalt ductility is measured according to T 0605-2011. Storage stability is tested according to T0661-2011.

[0048] Table 1 Performance test .

[0049] By comparing the test results of the embodiment and the comparative example, it can be seen that: first, the nano-silica particles are coated with a thickener that is easily soluble in xylene and cycloalkanoate, which is conducive to the complete implementation of the next grafting reaction, and the nano-silica is grafted and modified by using the macromolecular cycloalkanoate. With the advantages of large molecular weight, long organic side chain and good miscibility with matrix asphalt, the modified nano-silica particles are interspersed and entangled with the matrix asphalt and SBS three-dimensional network structure, which can solve the problem of poor storage stability of nano-modified asphalt caused by different densities between nano-silica particles and asphalt, increase the softening point of nano-modified asphalt, increase the elongation at 5°C, improve the high temperature performance and low temperature performance of nano-silica modified asphalt, and at the same time, the improvement of storage stability prevents stratification between nanomaterials and modified asphalt, so that nano-silica can be in contact with air over a large area, thereby improving the anti-aging performance of modified asphalt. In addition, the patent of the present invention also uses silane coupling agent and stearic acid to modify nano-silica respectively. Since the molecular weight of silane coupling agent and stearic acid are relatively low and do not contain long organic side chains, they cannot be entangled with the matrix asphalt and SBS network structure, and cannot solve the problem of density difference between nano-silica particles and modified asphalt. It is further found that the above-mentioned preparation steps and preparation methods have a synergistic and interrelated effect, which jointly improves the problem of density difference between nano-silica and modified asphalt, and the preparation method is simple.

[0050] The above is only a preferred embodiment of the present invention, and does not limit the present invention in other forms. Any technician familiar with the profession may use the above disclosed technical content to change or modify it into an equivalent embodiment with equivalent changes. However, any simple modification, equivalent change and modification made to the above embodiment according to the technical essence of the present invention without departing from the technical solution of the present invention still belongs to the protection scope of the technical solution of the present invention.

Claims

1. A method for modifying nano silicon dioxide, characterized in that: The following steps are involved: 1) The nano-silica and the thickener dispersion are stirred and mixed for 30-60 minutes, and then separated, washed and dried to obtain the nano-silica coated with the thickener; wherein the thickener is a polyethylene glycol aqueous solution with a weight concentration of 1-3%; 2) Adding nano-silica coated with a thickener to a cyclopentane acid solution with a weight concentration of 15-25%, reacting at a constant temperature of 60-80° C. for 180-240 minutes, separating, washing and drying to obtain modified nano-silica; wherein the solvent in the cyclopentane acid solution is a benzene solvent.

2. The method for modifying nano silicon dioxide according to claim 1, characterized in that: The polyethylene glycol in step 1) is one or both of PEG-4000 and PEG-6000.

3. The method for modifying nano silicon dioxide according to claim 1, characterized in that: The polyethylene glycol aqueous solution described in step 1) is prepared by mixing deionized water and a thickener, and then mixing at 50-70° C. and a stirring speed of 300-500 rpm for 20-40 minutes.

4. The method for modifying nano silicon dioxide according to claim 1, characterized in that: The stirring and mixing speed in step 1) is 4000-6000 rpm.

5. The method for modifying nano silicon dioxide according to claim 1, characterized in that: The benzene solvent in step 2) is xylene.

6. A modified asphalt, characterized in that: The raw materials include, by weight: 85-92 parts of base asphalt, 4-8 parts of modifier, 1-4 parts of solubilizer, 0.2-0.3 parts of stabilizer and 1.7-4.8 parts of the nano silicon dioxide described in any one of claims 1-5.

7. The modified asphalt according to claim 6, characterized in that: The solubilizing agent is naphthenic oil, and its kinematic viscosity at 40°C is less than 50 mm 2 / s.

8. The modified asphalt according to claim 6, characterized in that: The modifier is SBS polymer.

9. The modified asphalt according to claim 6, characterized in that: The preparation method comprises the following steps: 1) Mix the base asphalt and the solubilizer at 170-180°C and a stirring speed of 800-1000 rpm for 30-50 min, add nano-silicon dioxide, and react at 170-180°C and a stirring speed of 3000-4000 rpm for 20-40 min; 2) Add the modifier, react at 170-180°C and stirring speed of 3000-4000 rpm for 60-80 minutes, and then place in an oven at 140-150°C for constant temperature development for 60-100 minutes to obtain modified asphalt.

10. The modified asphalt according to claim 9, characterized in that: The base asphalt in step 1) is kept at a constant temperature of 130-140° C. for 40-50 minutes before mixing.

Citation Information

Patent Citations

  • Surface modification method of nanosilicon dioxide

    CN103013182A

  • A polymer-modified bitumen waterproof membrane and its preparation method

    CN108274844B

  • Glass fibre / vinyl ester resin composite material with interface modification by nanometer SiO2 and preparation method thereof

    CN106519587A

  • Method for improving polyethylene glycol phase change material performance by using modified silicon dioxide and phase change material

    CN106867467A

  • Preparation method for modified nanometer silicon dioxide

    CN106947291A

Cited By

  • Asphalt with high softening point temperature and preparation method thereof

    CN120988500A